- Equations and Applications
- Home
- Additive property of equality with decimals
- Multiplicative property of equality with decimals
- Multiplicative property of equality with whole numbers: Fractional answers
- Multiplicative property of equality with fractions
- Using two steps to solve an equation with whole numbers
- Solving an equation with parentheses
- Solving a fraction word problem using a linear equation of the form Ax = B
- Translating a sentence into a multi-step equation

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

# Solving an equation with parentheses Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Solving an equation with parentheses**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

### Answer : A

### Explanation

**Step 1:**

Given $7(p + 6) = 28$

Dividing both sides by 7

$\frac{7(p + 6)}{7} = \frac{28}{7}; \: (p + 6) = 4$

**Step 2:**

Subtracting 6 from both sides

$p + 6 − 6 = 4 − 6 = −2$

So, $p = −2$

### Answer : B

### Explanation

**Step 1:**

Given $5(m + 7) = 35$

Dividing both sides by 5

$\frac{5(m + 7)}{5} = \frac{35}{5}; \: (m + 7) = 7$

**Step 2:**

Subtracting 7 from both sides

$m + 7 − 7 = 7 − 7 = 0$

So, $m = 0$

### Answer : D

### Explanation

**Step 1:**

Given $13(g − 2) = 52$

Dividing both sides by 13

$\frac{13(g − 2)}{13} = \frac{52}{13}; \: (g − 2) = 4$

**Step 2:**

Adding 2 to both sides

$g + 2 − 2 = 4 + 2 = 6$

So, $g = 6$

### Answer : C

### Explanation

**Step 1:**

Given $27 = 9(w − 5)$

Dividing both sides by 9

$\frac{9(w − 5)}{9} = \frac{27}{9}; \: (w − 5) = 3$

**Step 2:**

Adding 5 to both sides

$w + 5 − 5 = 3 + 5 = 8$

So, $w = 8$

### Answer : B

### Explanation

**Step 1:**

Given $7(k − 13) = 0$

Dividing both sides by 7

$\frac{7(k − 13)}{7} = \frac{0}{7}; \: (k − 13) = 0$

**Step 2:**

Adding 13 to both sides

$k + 13 − 13 = 0 + 13 = 13$

So, $k = 13$

### Answer : A

### Explanation

**Step 1:**

Given $2(n − 5) = −8$

Dividing both sides by 2

$\frac{2(n − 5)}{2} = \frac{−8}{2}; \: (n − 5) = −4$

**Step 2:**

Adding 5 to both sides

$n + 5 − 5 = −4 + 5 = 1$

So, $n = 1$

### Answer : D

### Explanation

**Step 1:**

Given $−12 = 3(c + 4)$

Dividing both sides by 3

$\frac{−12}{3} = \frac{3(c + 4)}{3}; \: (c + 4) = −4$

**Step 2:**

Subtracting 4 from both sides

$(c + 4 − 4) = −4 −4 = −8$

So, $c = −8$

### Answer : C

### Explanation

**Step 1:**

Given $35 = 7(w − 2)$

Dividing both sides by 7

$\frac{35}{7} = \frac{7(w − 2)}{7}; \: (w − 2) = 5$

**Step 2:**

Adding 2 to both sides

$w + 2 − 2 = 5 + 2 = 7$

So, $w = 7$

### Answer : B

### Explanation

**Step 1:**

Given $2(y − 4) = −10$

Dividing both sides by 2

$\frac{2(y − 4)}{2} = \frac{−10}{2}; \: (y − 4) = −5$

**Step 2:**

Adding 4 to both sides

$y + 4 − 4 = −5 + 4 = −1$

So, $y = −1$

### Answer : A

### Explanation

**Step 1:**

Given $4(p + 5) = 28$

Dividing both sides by 4

$\frac{4(p + 5)}{4} = \frac{28}{4}; \: (p + 5) = 7$

**Step 2:**

Subtracting 5 from both sides

$(p + 5 − 5) = 7 − 5 = 2$

So, $p = 2$